2004
DOI: 10.5465/ambpp.2004.13862408
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Trustworthiness of Knowledge Sources: The Moderating Impact of Relationship Length.

Abstract: Prior meta-analytic evidence has indicated no association between relationship length and perceived trustworthiness. Viewing trustors as information processors, the authors propose a model in which relationship length, although having no direct effect on perceived trustworthiness, moderates the association between perceived trustworthiness and the basis on which people decide to trust each other. Specifically, as trustors learn about others, they base their trust on different kinds of information (demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
158
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(163 citation statements)
references
References 21 publications
5
158
0
Order By: Relevance
“…Overall, familiar candidates were not helped by facial similarity. As in previous research (Levin, Whitener, and Cross 2006), similarity is a heuristic which is relied upon more in unfamiliar relationships than in familiar ones. In all three studies (as well as the previous pilot study), the effect of facial similarity was heightened when other competing identity cues were less salient.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, familiar candidates were not helped by facial similarity. As in previous research (Levin, Whitener, and Cross 2006), similarity is a heuristic which is relied upon more in unfamiliar relationships than in familiar ones. In all three studies (as well as the previous pilot study), the effect of facial similarity was heightened when other competing identity cues were less salient.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown that over the course of a team's lifecycle, the enablers of trust change. Dispositional factors and perceived similarity between team members drive initial trust perceptions, while indicators of trustworthiness and actual behavior are the basis for trust later on in the team's lifecycle (Levin, et al, 2006). This suggests that collaborative tools features that allow for individuals to share common backgrounds and similarities should promote trust for ad-hoc military teams.…”
Section: Trust and Military Team Performancementioning
confidence: 99%
“…On the other hand, frequency has also been associated with future commitment to continue the relationship (Bonner and Calantone 2005;goodman and Dion 2001;Hoetker et al 2007;Lusch and Brown 1996;Sharfman and Dean Jr 1997), and the importance of frequency has been highlighted in the relationships between agents and the generation of such trust (Levin et al 2006;Wang et al 2006).…”
Section: Characteristics Of the Relationshipmentioning
confidence: 99%
“…in this regard, Caves and Bradburd (1988) justify that the transmission of information is more efficient through the vertical integration of its best qualities of coordination. However, on the other hand, the transmission of information enhances the relational environment (Brush and Rexha 2007;Mukherji and Francis 2003;Patnayakuni et al 2006;Rodríguez del Bosque Rodríguez et al 2006), the commitment between parties (Kent and Mentzer 2003) and the generation of trust (Achim 2003;Hartmann and Apaolaza ibáñez 2007;Levin et al 2006;Wang et al 2006;Yang et al 2008).…”
Section: Characteristics Of the Relationshipmentioning
confidence: 99%